Fathers' postnatal mental health and child wellbeing at aged five: The mediating role of parental self-efficacy and parenting behaviour. - D'Esposito, F; Cooklin, A R; Wade, C; Nicholson, J; Giallo, R (My University, 2011)
Background: Fathers' postnatal mental health difficulties have been associated with both short- and long-term emotional and behavioural outcomes for children. The mechanisms or pathways by which fathers' mental health may contribute to outcomes for children have received little attention. One pathway is likely to be via the negative effects of mental health difficulties on parenting behaviours important for promoting child wellbeing and development, however, these associations have yet to be substantiated longitudinally or with fathers. Aim: To explore the longitudinal relationships between fathers’ postnatal mental health, parenting and emotional-behavioural outcomes for children at aged five. Study Design: Secondary analysis of data from fathers participating in the Growing Up in Australia: the Longitudinal Study of Australian Children was conducted. Participants were 2025 fathers in a couple relationship who had complete data on measures of psychological distress, parental self-efficacy, parenting warmth and irritability. Mothers' reports of children's emotional and behavioural functioning was used. Data were from three waves of data collection when the children were aged 0-1, 2-3 and 4-5 years. Results: Path analysis and latent growth modelling revealed that the relationship between fathers' postnatal psychological distress and emotional-behavioural outcomes for children at age five was mediated by parental self-efficacy (PSE) and parenting behaviour. Specifically, fathers’ psychological distress was associated with low PSE in the postnatal period and a decline across the early childhood period. Low postnatal PSE and over time was in turn predictive of low parenting warmth and high parenting irritability when the children were aged five. Low postnatal PSE and decline over time, low warmth and high irritability were associated with increased child emotional and behavioural difficulties after controlling for concurrent fathers’ mental health. These relationships were also maintained after accounting for the relationship between mothers' postnatal mental health and child outcomes. Conclusions: These findings underscore the contribution of fathers’ early mental health and PSE to later parenting behaviour and child outcomes, further highlighting the importance of providing mental health and parenting support in the early parenting years. Implications for policy and practice are discussed, with particular focus on improving mental health and parenting support to fathers in the early childhood period.
Keywords: Health -- Mental; Families -- Fathers; Families and relationships; Health and wellbeing; Families; Health; Fathers; Mental; Families and relationships; Health and wellbeing